Myocardial Adaptation to High-Intensity (Interval) Training in Previously Untrained Men With a Longitudinal Cardiovascular Magnetic Resonance Imaging Study (Running Study and Heart Trial). (April 2015) - Scharf, Michael; Schmid, Axel; Kemmler, Wolfgang; von Stengel, Simon; May, Matthias S.; Wuest, Wolfgang; Achenbach, Stephan; Uder, Michael; Lell, Michael M.
<x xml:space="preserve">Abstract</x> Background— To prospectively evaluate whether short-term high-intensity (interval) training (HI(I)T) induces detectable morphological cardiac changes in previously untrained men in cardiovascular magnetic resonance imaging. Methods and Results— Eighty-four untrained volunteers were randomly assigned to a HI(I)T group (n=42; 44.1±4.7 years) or an inactive control group (n=42; 42.3±5.6 years). HI(I)T focused on interval runs (intensity: 95%–105% of individually calculated heart rate at the anaerobic threshold). Before and after 16 weeks, all subjects underwent physiological examination, stepwise treadmill test with blood lactate analysis, and contrast-enhanced cardiovascular magnetic resonance imaging (cine, tagging, and delayed enhancement). Indexed left ventricular (LV) and right ventricular (RV) volume (LV, 77.1±8.5–83.9±8.6; RV, 80.5±8.5–86.6±8.1) and mass (LV, 58.2±6.4–63.4±8.1; RV, 14.8±1.7–16.1±2.1) significantly increased with HI(I)T. Changes in LV and RV morphological parameters with HI(I)T were highly correlated with an increase in maximal aerobic capacity (VO2max) and a decrease in blood lactate concentration at the anaerobic threshold. Mean LV and RV remodeling index of HI(I)T group did not alter with training (0.76 ±0.09 and 0.24±0.10 g/mL, respectively [P=0.97 and P=0.72]), indicating balanced cardiac adaptation. Myocardial circumferential strain decreased after HI(I)T within all 6 basal segments (anteroseptal, P=0.01 and anterolateral, P<0.001). There was no late gadolinium enhancement in any of the participants before or post HI(I)T. Conclusions— Sixteen weeks of HI(I)T lead to measurable changes in cardiac atrial and ventricular morphology and function in previously untrained men. This correlates with improvements in parameters of endurance capacity. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01406730.